# Solve for z 39z+91a=71*13

39z+91a=71⋅13
Multiply 71 by 13.
39z+91a=923
Subtract 91a from both sides of the equation.
39z=923-91a
Divide each term by 39 and simplify.
Divide each term in 39z=923-91a by 39.
39z39=92339+-91a39
Cancel the common factor of 39.
Cancel the common factor.
39z39=92339+-91a39
Divide z by 1.
z=92339+-91a39
z=92339+-91a39
Simplify each term.
Cancel the common factor of 923 and 39.
Factor 13 out of 923.
z=13(71)39+-91a39
Cancel the common factors.
Factor 13 out of 39.
z=13⋅7113⋅3+-91a39
Cancel the common factor.
z=13⋅7113⋅3+-91a39
Rewrite the expression.
z=713+-91a39
z=713+-91a39
z=713+-91a39
Cancel the common factor of -91 and 39.
Factor 13 out of -91a.
z=713+13(-7a)39
Cancel the common factors.
Factor 13 out of 39.
z=713+13(-7a)13(3)
Cancel the common factor.
z=713+13(-7a)13⋅3
Rewrite the expression.
z=713+-7a3
z=713+-7a3
z=713+-7a3
Move the negative in front of the fraction.
z=713-7a3
z=713-7a3
z=713-7a3
Solve for z 39z+91a=71*13

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top